Normative Divergence on Consensual Homosexuality: A Comparative Study of Islamic Criminal Law and Indonesian Positive Law - M. Nurul Irfan; Laila Palupi Rahmadani; Maskur Rosyid; Harapandi Dahri; Shalini Urteaga-Crovetto (Indonesian Journal of Islamic Law, 2025)
The criminalisation of liwāṭ in Islamic criminal law is grounded in a robust normative framework. However, it contains a dialectic between the determination of ḥudūd and the discretion of taʿzīr, with the principle that darʾ al-ḥudūd bi al-shubuhāt prevents criminalisation when there is doubt. In contrast, Indonesian positive law explicitly does not criminalise consensual same-sex relations between adults because the principle of legality requires the formulation of a written, clear, and definite criminal offence. This absence of norms is not a legislative omission but rather a policy choice that creates legal ambiguity as a control mechanism, achieved indirectly through other legal regimes. This study employs a normative and comparative juridical approach, focusing on the textual interpretation of Islamic criminal law and national statutory provisions. The results show that the tension between the certainty of criminalisation in Islamic criminal law and the ambiguity of Indonesian positive law illustrates two different models of social control: cautious normative certainty versus managed normative absence. The primary contribution of this research is to offer a new conceptual framework by repositioning the "legal vacuum" not simply as the absence of criminal norms at the national level, but as a government strategy based on legal ambiguity in responding to the prescriptivity of Sharia norms. Based on this analysis, the precautionary principle of sentencing in Islamic criminal law has the potential to serve as a basis for harmonisation that aligns with the principles of legality and human rights protection in the national legal system, thereby opening up space for reconciliation between Islamic moral norms and the constitutionality of law in Indonesia.